Married Women's Economic Independence and Divorce in the Nineteenth- and Early-Twentieth-Century United States. Issue 3 (22nd June 2018) - MacDonald, Daniel; Dildar, Yasemin
Abstract : We analyze the effects of the Married Women's Property Acts and Earnings Acts (EAs) on divorce rates in the late-nineteenth- and early-twentieth-century United States. We find that the property acts increased divorce rates, which is consistent with the predicted outcome, in household extensive bargaining models, of an increase in the married woman's relative bargaining power. We also find some evidence that the EAs had a positive effect on divorce rates, though it is not statistically significant after accounting for the possibility that divorce rates changed prior to the enactment of an EA. To support our causal argument, we control for regional trends in the divorce rate and account for the timing of the laws' effects. We also assess alternative explanations for the rise in divorce rates during the late nineteenth century, including age structure, divorce law, urbanization, economic development, and foreign immigration, and we find that only age structure and urbanization positively affected divorce rates along with the property acts. Finally, we provide support for our argument from court cases in which the acts were used to defend a woman's property rights against claims from her ex-husband.